The Project P.A.T.H.S. in Hong Kong—Lessons Learned and Implications for Positive Youth Development Programs - Daniel T. L. Shek; Rachel C. F. Sun (The Scientific World Journal)
The Project P.A.T.H.S. is a positive youth development program which attempts to promote holistic development of junior secondary schools in Hong Kong. It is ground breaking in terms of the number of schools participating in the project and financial resources injected into the project. Based on the experiences gained from the implementation of the project and evaluation data collected from 2005 to 2011, several issues pertinent to the development of positive youth development programs in the Chinese culture are discussed. These issues include complexity of program development, importance of training, identification of factors governing program implementation, need for evaluation, and promotion of sustainability of the program in the long run.